Tradition and Modernization. Contemporary Hungarian Popular Cinema - Varga, Balázs (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2013)
This article provides an overview of the recent trends and problems of Hungarian popular cinema with special regard to its cultural context outlining the process of recognition of popular cinema over the past twenty years in Hungary. In general Hungarian cinema is characterised by middle-range genres (dominantly comedy) and not by a large scope. This was the case in the 1930s and 1940s during the ’golden age’ of Hungarian comedies and popular cinema. And this typifies contemporary Hungarian popular cinema as well. However, the first decade after the political changes, the 1990s was characterised by a return to the tradition of the classical Hungarian comedies and only the 2000s brought the modernization of Hungarian popular cinema.

Artykuł dostarcza informacji na temat ostatnich trendów oraz problemów związanych z węgierskim kinem popularnym ze szczególnym uwzględnieniem kulturowego kontekstu, w jakim funkcjonuje kino popularne na Węgrzech w ciągu ostatnich dwudziestu lat. Kino węgierskie charakteryzuje się dominacją średniobudżetowego kina gatunków (przede wszystkim komedii). Zjawisko to stanowi powtórzenie fenomenu dominacji tego rodzaju filmów w latach 30. i 40. uznawanych za „złoty wiek” węgierskiej komedii i węgierskiego kina popularnego. W dekadzie lat 90. dało się zaobserwować powrót to tradycji klasycznej komedii, natomiast w dekadzie następnej zauważalny jest rosnący stopień nowoczesnego myślenia o kinie oraz innowacji w obrębie gatunku.
Keywords: Hungrian film market; Hungarian cinema after transition; Eastern European cinema; węgierski rynek filmowy; kino węgierskie po transformacji; kino Europy Środkowo-Wschodniej